On the rate of convergence in the invariance principle for weakly dependent random variables - Mukhamedov, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 519.21We consider nonstationary sequences of $φ$-mixing random variables. By using the Levy–Prokhorov distance, we estimate the rate of convergence in the invariance principle for nonstationary $φ$-mixing random variables. The obtained results extend and generalize several known results for nonstationary $φ$-mixing random variables.